Brain Aging: Key Theories and Neurophysiological Insights - V.D. Tretyakova; K.I. Pultsina (Клиническая и специальная психология)
In recent years, the problem of brain aging is becoming more and more relevant due to the increasing proportion of elderly people in the population. One of the key issues in this area is the study of the effect of aging on cognitive functions and brain activity, since these functions play an important role in everyday life and determine a person’s ability to lead a full, independent life and adapt to a changing environment. The aim of this article was to review foreign literature concerning the main theories of cognitive aging such as the frontal cortex aging theory, compensatory theories, reserve theory, sensory deprivation theory, information processing speed reduction theory and inhibitory influence deficit theory. Particular attention is paid to the neurophysiological aspects of aging. The literature search was carried out by keywords using the Google Scholar and PubMed databases. The reviewed results of neurocognitive studies allow us to identify structural and functional changes in the brain during aging, which can help clinical specialists differentiate “normal” aging from possible signs of brain diseases and develop a more individual approach if necessary to correct cognitive impairment.